New reliable biochemical marker for screening 21α-hydroxylase deficiency without index person among hirsute women in agreement with HLA-haplotyping - Chryssikopoulos, A.; Phocas, I.; Sarandakou, A.; Trakakis, E.; Rizos, D. (Journal of Endocrinological Investigation, 1995)
Late onset congenital adrenal hyperplasia due to 21α-hydroxylase deficiency (LO21OH def), as many other diseases, is the cause of hirsutism, menstrual disorders, infertility (PCO-like symptoms). We evaluated the reliability of a new biochemical marker for screening LO-21OH def in 47 women with PCO-like symptoms and 11 men, members of their families, comparing the results of separation using this new marker with those of HLA-haplotyping in 21 members of the patient population. All subjects were stimulated with 0.25 mg synthetic ACTH iv. Serum progesterone (P), 17-hy-droxyprogesterone (17-OHP) and cortisol (F) at 0, 15, 30, 45 and 60 min following ACTH administration were determined and the new marker, namely the difference between 60min and 0min of the ratio F/17-OHP [Δ F/17-OHP (60 min–0 min)] was calculated. According to the established biochemical criteria for the detection of LO-21OH def cases, (Gutai 30 min ≥12 ng/dl/min and 17-OHP 60 min ≥12 ng/ml for severe 21-OH def and Gutai 30 min<6.5 ng/dl/min and 17-OHP 60 min<5 ng/ml for “healthy” individuals regarding 21-OH def) two groups, A and B respectively, were separated from the patient population. In group A (n=8), with LO-21 OH def, the new marker showed negative values in all cases, while in group B (n=9), without LO-21 OH def, this marker was positive. The remaining subjects, depending on the results of the new marker were separated in 2 subgroups, Cneg (n=28), with negative values, composed, consequently, of members with 21-OH def and Cpos (n=13), with positive values, composed, consequently, of subjects with absence of LO-21OH def. HLA-typing was in agreement with the results of screening by the new marker, in 20 out of 21 cases, while there was only one false negative result. In conclusion, the proposed biochemical marker ΔF/17-OHP (60 min–0 min) seems to be a reliable parameter for the LO-21OH def detection among young women with PCO-like symptoms as well as males suspected for congenital adrenal hyperplasia. © 1995, Italian Society of Endocrinology (SIE). All rights reserved.
Keywords: hirsutism; late-onset 21-OH deficiency; women with PCO-like symptoms